The Art of Communication in a Polarized World - Conway, Kyle (Athabasca University Press, 2020)
People's minds are hard to change. In North America and elsewhere, communities are fractured along ideological lines as social media and algorithms encourage individuals to seek out others who think like they do and to condemn those that don't. This social and political polarization has resulted in systemic discrimination and weaponized communication trends such as gaslighting and fake news. In this compelling new book, Kyle Conway confronts the communication challenges of our modern world by navigating the space between opposing perspectives. Conway explores how individuals can come to understand another person's interpretation of the world and provides the tools for shaping effective arguments capable of altering their perspective. Drawing on the theory of cultural translation and its dimensions of power, meaning, and invention, Conway deepens our understanding of what it means to communicate and opens the door to new approaches to politics and ethics. An essential guide for surviving in our polarized society, this book offers concrete strategies for refining how values and ideas are communicated.